Roedores y murciélagos en la zona cafetalera del VolcaÌn TacanaÌ, Chiapas, México - Mendoza SaÌenz, Víctor Hugo; HorvaÌth, Anna (THERYA, 2013)
We assessed the species richness, assemblage composition and the conservation status of small rodents and bats in the protected area of the Volcano Tacaná Biosphere Reserve in Chiapas, Mexico. Data were collected in shade-coffee plantations and cloud forest by live capture and release techniques for small mammals. Species richness, indexes of diversity and similarity as well the diversity of guild structure of foraging space use were analyzed among the studied assemblages. We captured 16 bat and nine rodent species recording a total of 25 small mammal species, two of them corresponding to a category of conservation endangerment in the NOM-059-2010. In the cloud forest we observed lower species richness but higher abundance, with differences between diversity patterns of rodents and bats. The assemblage of rodents was more diverse in the forest and we observed a high degree of complementarity between forest and coffee-plantations. The assemblages of bats showed no difference in their diversity; however, coffee plantation has higher species richness and the assemblages showed a nested pattern in their composition. In the cloud forest we found a higher diversity in those guilds that have resource-requirements associated with habitat complexity and canopy cover, while in the coffee-plantations we found a higher diversity in those guilds whose requirements are associated with open areas. Our results indicate that both rodents and bats respond in a different manner to the alteration of habitat caused by coffee-plantations and high lights the importance of conserving all of the remaining native forest patches in the Tacaná region, in order to assure the survival of these fragile populations of small mammals. Key words: Chiroptera, guild, Rodentia, small mammal assemblage, Tacana Volcano Biosphere Reserve.